1999
DOI: 10.1091/mbc.10.11.3979
|View full text |Cite
|
Sign up to set email alerts
|

Di-Leucine Signals Mediate Targeting of Tyrosinase and Synaptotagmin to Synaptic-like Microvesicles within PC12 Cells

Abstract: One pathway in forming synaptic-like microvesicles (SLMV) involves direct budding from the plasma membrane, requires adaptor protein 2 (AP2) and is brefeldin A (BFA) resistant. A second route leads from the plasma membrane to an endosomal intermediate from which SLMV bud in a BFA-sensitive, AP3-dependent manner. Because AP3 has been shown to bind to a di-leucine targeting signal in vitro, we have investigated whether this major class of targeting signals is capable of directing protein traffic to SLMV in vivo.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
61
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 71 publications
2
61
0
Order By: Relevance
“…The kinase extensively colocalizes with AP-3 and ZnT3 and to a lower extent with AP-1. A-C to AЈ-CЈ series represent two optical planes taken every 0.75 m. Bar, 6 m. been described in the Golgi complex (Wang et al, 2003), synaptic vesicles (Guo et al, 2003), and endosomes (Balla et al, 2002), an organelle that in PC12 cell gives raise to microvesicles by AP-3-dependent mechanisms (Faundez et al, 1997;Shi et al, 1998;Blagoveshchenskaya et al, 1999;Salazar et al, 2004a,b). As a first step to determine the potential localization of PI4KII␣ to AP-3-derived vesicles, fractions from PC12 cell glycerol velocity gradients and isopycnic sucrose gradients leading to the ZnT3-enriched vesicle preparation ( Figure 1C) were probed with antibodies directed against PI4KII␣.…”
Section: Pi4kii␣ Is Present In Ap-3-derived Vesiclesmentioning
confidence: 99%
See 1 more Smart Citation
“…The kinase extensively colocalizes with AP-3 and ZnT3 and to a lower extent with AP-1. A-C to AЈ-CЈ series represent two optical planes taken every 0.75 m. Bar, 6 m. been described in the Golgi complex (Wang et al, 2003), synaptic vesicles (Guo et al, 2003), and endosomes (Balla et al, 2002), an organelle that in PC12 cell gives raise to microvesicles by AP-3-dependent mechanisms (Faundez et al, 1997;Shi et al, 1998;Blagoveshchenskaya et al, 1999;Salazar et al, 2004a,b). As a first step to determine the potential localization of PI4KII␣ to AP-3-derived vesicles, fractions from PC12 cell glycerol velocity gradients and isopycnic sucrose gradients leading to the ZnT3-enriched vesicle preparation ( Figure 1C) were probed with antibodies directed against PI4KII␣.…”
Section: Pi4kii␣ Is Present In Ap-3-derived Vesiclesmentioning
confidence: 99%
“…This drug blocks AP-1 (Robinson and Kreis, 1992) and AP-3 recruitment to membranes and robustly inhibits the formation of vesicles generated by AP-3-dependent mechanisms (Faundez et al, 1997;Shi et al, 1998;Blagoveshchenskaya et al, 1999;Salazar et al, 2004a,b). In contrast, it does not affect formation of AP-2-derived SLMVs (Faundez et al, 1997;Shi et al, 1998;Blagoveshchenskaya et al, 1999;Salazar et al, 2004a,b). As expected, the ZnT3 containing peak in glycerol velocity gradients almost disappeared after BFA treatment.…”
Section: Ap-3-dependent Targeting Of Pi4kiiamentioning
confidence: 99%
“…On the one hand, this model has been useful for elucidating SLMV targeting sequences for synaptic vesicle proteins, such as synaptobrevin and synaptotagmin (6,7). It is assumed that SLMV targeting sequences in PC12 cells would correspond to synaptic vesicle targeting sequences in neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Thus PC12 cells have been used as an in vitro model for studying the biogenesis of SVs/SLMVs. Using this cell type, targeting signals have been identified in the amino acid sequence of the synaptic vesicle proteins VAMPII/ synaptobrevin (6) and synaptotagmin (7). These studies, however, have not identified a universal targeting signal.…”
mentioning
confidence: 99%
“…The group of nonsynaptic vesicle proteins localized in SLMVs can be further divided into the nonneuronal paralogs of synaptic vesicle proteins (cellubrevin, cellugyrin, and pantophysin) (14 -16) and those proteins that are unrelated to synaptic vesicle proteins (tyrosinase and P-selectin) (13,17). These studies, which examined targeting motifs, failed to identify a universal sequence applicable to all SLMV proteins.…”
mentioning
confidence: 99%